2007
DOI: 10.1590/s1413-85572007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in online collaborative learning groups promoting affective education and social capital

Abstract: This paper reports the results of a study aimed to establish whether the amount and types of conflicts vary in all male, all female and mixed gender groups working in asynchronous collaborative learning online settings. Sixty psychology majors were divided into three groups conducted online by the same teacher. The study show that the levels of participation in the three groups varied in relation to gender composition. Further the results evidenced all female group did have more conflicts then male and mixed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It was found that the mean scores for all variables were higher for female than for the male respondents. Ella, Roberta, Andrea, & Manuela (2007) also found in their study that female learners do show to have more conflicts than their male counterparts.…”
Section: Summary Of Findings and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It was found that the mean scores for all variables were higher for female than for the male respondents. Ella, Roberta, Andrea, & Manuela (2007) also found in their study that female learners do show to have more conflicts than their male counterparts.…”
Section: Summary Of Findings and Discussionmentioning
confidence: 74%
“…However, when several individuals are put together to complete tasks, sometimes conflicts arise. This paper by Ella, Roberta, Andrea, & Manuela (2007) reports the results of a study aimed to establish whether the amount and types of conflicts vary in all male, all female and mixed gender groups working in asynchronous collaborative learning online settings. Sixty psychology majors were divided into three groups.…”
Section: Past Studiesmentioning
confidence: 99%